2011
DOI: 10.1111/j.1365-2265.2011.03990.x
|View full text |Cite
|
Sign up to set email alerts
|

High plasma retinol binding protein 4 (RBP4) is associated with systemic inflammation independently of low RBP4 adipose expression and is normalized by transplantation in nonobese, nondiabetic patients with chronic kidney disease

Abstract: High plasma RBP4 and inflammation are clustered in CKD in the absence of obesity and diabetes and are normalized by transplantation. Adipose RBP4 expression is not involved in plasma RBP4 elevation, which appears to be mainly because of passive accumulation, or in CKD-associated inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
(66 reference statements)
3
11
0
Order By: Relevance
“…Therefore, we speculate that RBP4 is not a biomarker of LVD but that this adipokine may simply accumulate in the circulation in advanced HF, as a consequence of kidney function deterioration clinically manifested by cardiorenal syndrome. This hypothesis is supported by studies reporting elevated plasma RBP4 levels in CKD [27][28][29], and its normalization after kidney transplantation [30,31], as well as the results of the multivariate regression analysis in the presented study. Further evidence can be seen with normal RBP4 levels in patients with Table 3.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Therefore, we speculate that RBP4 is not a biomarker of LVD but that this adipokine may simply accumulate in the circulation in advanced HF, as a consequence of kidney function deterioration clinically manifested by cardiorenal syndrome. This hypothesis is supported by studies reporting elevated plasma RBP4 levels in CKD [27][28][29], and its normalization after kidney transplantation [30,31], as well as the results of the multivariate regression analysis in the presented study. Further evidence can be seen with normal RBP4 levels in patients with Table 3.…”
Section: Discussionsupporting
confidence: 77%
“…A study performed in normal-weight, nondiabetic CKD subjects proved that RBP4 plasma elevation could be an effect of passive accumulation of transthyretin (TTR) -the protein that carries RBP4 bound to retinol in circulation, and prevents its filtration in the kidneys [30]. It has been shown that fenretinide (a synthetic retinoid that disrupts binding of RBP4 to TTR) enhances renal excretion and leads to decreased RBP4 concentration levels in mice [31].…”
Section: Discussionmentioning
confidence: 99%
“…RBP-4 levels were significantly decreased following weight loss after a bariatric surgery (Haider et al, 2007; Gomez-Ambrosi et al, 2008; Tschoner et al, 2008). Barazzoni et al (2011) showed that high plasma RBP-4 levels was correlated with high systemic inflammatory responses in non-obese, non-diabetic patients with chronic kidney disease (But the correlation was independent of RBP-4 expression in adipose tissue. More studies are required to investigate the roles of RBP-4 in inflammation.…”
Section: The Changes Of Novel Adipokines After Bariatric Surgery and mentioning
confidence: 99%
“…Nonetheless, positive associations were documented for circulating RBP4 or RBP4 expression levels with established CVD risk factors, including metabolic syndrome, 6, 7, 15 overall/central obesity, 1518 dyslipidemia, 3, 5, 6, 11, 15, 18, 19 inflammatory markers, 2022 and hypertension. 18, 23 Moreover, RBP4 levels have been positively associated with carotid intima-media thickness 23, 24 and prevalent CVD events.…”
mentioning
confidence: 99%